Production cross sections and isomeric ratios for the isomeric pair 89m Nb and 89g Nb in the 90Zr (d, 3n) 89m/g Nb reaction - Herreros Usher, O. R.; Arizmendi, C. M.; Wasilevsky de Lammirato, Catalina; Jorge Nassiff, Sonia (1976)
Fil: Herreros Usher, O.R. Comisión Nacional de Energía Atómica, Argentina